2009
DOI: 10.4076/1752-1947-3-8246
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and mammographic appearance of dermatofibrosarcoma protuberans in a male breast: a case report and literature review

Abstract: IntroductionDermatofibrosarcoma protuberans is a rare low-grade soft tissue neoplasm with trunk and extremities being the most common sites of involvement. We report a rare case of male breast with dermatofibrosarcoma protuberans and its imaging features. To our knowledge the imaging appearance of dermatofibrosarcoma protuberans of the breast has never been reported in the literature.Case presentationWe report the imaging appearance of dermatofibrosarcoma protuberans on the breast of a 41-year-old Chinese man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…The distribution of DFSP between genders shows that women have higher incidence rates than men except among the elderly (15), which is in opposition to statements of other reports in which men are slightly more commonly affected than women (9). In our case, the tumor on the male breast appeared much later, at the age of 66, compared to the recently published review of Bouhani et al (7) who state that the mean age of DFSP in the male breast is 32.6 years.…”
Section: Case Reportcontrasting
confidence: 95%
See 1 more Smart Citation
“…The distribution of DFSP between genders shows that women have higher incidence rates than men except among the elderly (15), which is in opposition to statements of other reports in which men are slightly more commonly affected than women (9). In our case, the tumor on the male breast appeared much later, at the age of 66, compared to the recently published review of Bouhani et al (7) who state that the mean age of DFSP in the male breast is 32.6 years.…”
Section: Case Reportcontrasting
confidence: 95%
“…The most common presentation in a male's breast is a mass with extensive nodules on the surface (7). The tumor tends to spare adnexal structures and is commonly superficially located, but in recurrent cases and untreated tumors, it can spread to more deeply situated structures (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In their series of 11 people with DFSP, MRI was used in four, in which a well‐delimited, yet unspecific image of the tumor was obtained. Various cases have subsequently been published in which MRI was used preoperatively, demonstrating a certain efficacy, particularly in cases of large DFSP tumors 12–17 . The largest series is that of Torreggiani and colleagues, 17 who studied 10 cases of DFSP with MRI but were able to distinguish only between superficial and deep and between clearly and poorly delimited.…”
mentioning
confidence: 99%
“…DFSP is considered as radiosensitive tumor. 15 However, adjuvant radiotherapy is not extensively studied, even though it was found that has successfully contributed to local tumor control. 16 In the study of MD Anderson Cancer Center in 1998 the estimated rate of local control in 19 patients who received radiotherapy as adjuvant to surgical resection was 95% at 10 years.…”
Section: Discussionmentioning
confidence: 99%